Zoledronate and lipopolysaccharide suppress osteoblast differentiation through downregulating phosphorylation of Smad in pre-osteoblastic MC3T3-E1 cells. Issue 4 (July 2022) - Amamoto, Shinsuke; Yoshiga, Daigo; Tabe, Shirou; Kokabu, Shoichiro; Fujii, Wataru; Hikiji, Hisako; Tominaga, Kazuhiro; Yoshioka, Izumi
Abstract: Objective: It is crucial to treat Bisphosphonate-related osteonecrosis of the jaw (BRONJ), a serious problem; however, its pathogenesis is unclear. We have previously reported in vivo that bacterial infection or administration of lipopolysaccharide (LPS) aggravates BRONJ in rats. To elucidate the detailed mechanism of BRONJ, we investigated whether co-administration of LPS and zoledronate (ZOL) exacerbated the differentiation of pre-osteoblastic MC3T3-E1 cells in vitro . Methods: MC3T3-E1 cells were treated with ZOL, LPS, or both agents at a concentration gradient for the indicated times, after which cell viability was measured using the WST-8 assay. Osteogenic differentiation was assessed using alkaline phosphatase (ALP) staining, ALP activity assay, and Alizarin Red S staining. The expression of relevant genes was detected by quantitative real-time reverse-transcriptase polymerase chain reaction. Western blotting was performed to examine the phosphorylation levels of Smad1/5/8. Results: Co-administration of LPS and ZOL inhibited ALP activity and ALP staining more than a single administration of LPS or ZOL from the early stage of osteoblast differentiation. Co-administration of LPS and ZOL also inhibited the expression of osteoblast differentiation markers, Runx2, Col I, ALP, and BSP, as well as phosphorylation of Smad1/5/8 more than a single administration of LPS or ZOL. Conclusions: Our data suggest that ZOL and LPS have an inhibitory effect on osteoblast differentiation through BMP2-Smad signaling. This effect may have led to a decrease in mineralization in vitro, suggesting that in patients treated with ZOL, ZOL causes osteonecrosis in their oral cavities, where LPS is universally produced by bacteria.